Apport de l’analyse biomimétique à l’évaluation comparée de scénarios prospectifs en mobilité urbaine - Philippe Terrier; Mathias Glaus; Emmanuel Raufflet (Développement Durable et Territoires)
This article presents the use of the biomimetic approach to evaluate the environmental performance of scenarios for urban mobility services. A reference scenario and two prospective alternative scenarios for mobility in Montreal, Quebec, will be analyzed using the BiomiMETRIC tool. This tool allows the quantification of performance based on each of the ten biomimetic principles, using quantitative methods derived from life cycle analysis, supplemented by qualitative questions evaluated and weighted by the user. The comparative analysis of the reference initial scenario (0 Status Quo) with the two prospective mobility scenarios (1 Collective Transport and 2 Resilience Hazards) using the biomimetic approach leads to the conclusion that the prospective mobility scenarios require corrective action in terms of integrating the biomimetic principles 7 – Remain in dynamic equilibrium with the biosphere and 8 – Use waste as resources. However, the alternative scenarios result in an average reduction of impacts evaluated at 25 % and 59 % respectively compared to the 0 Status Quo scenario. The biomimetic approach offers a complementary angle of analysis for the evaluation of overall environmental performance to make decisions in a sustainable development perspective.